Răspunsuri

2014-05-05T12:29:56+03:00
1) (x+5)(x+1)-x(x+2)=20-x                                             2)(x-1)(x-4)-(x+2)(x+3)=4-2x             3)(x-3)(x-2)-(x+1)(2x-3)=1-x²                                         4)(x+5)²-2(x+1)(x-2)+(x+3)(x-3)=55-3x                                                                                                                                          5)(3x-1)²+(x-2)(2x+3)=(3x+2)(3x-2)+2(x-2)²-15            6)(x-rd5)²-(x+rd5)²=rd20                   7)  (4x+3)²-(x-1)(x-3)=(4x+1)(4x-1)-(x+5)(x-2)+2(15x+2)                                                         8)(x+rd3)(x-rd3)_(x-rd3)²=12                                        9)  rd7x-3rd7=9-x                              10)      (x+rd2)(x-rd2)-(x-rd2)²=(x+rd2)²-x²-x